Influence of Rice Husk and Wood Biomass Properties on the Manufacture of Filaments for Fused Deposition Modeling - Le Guen, Marie-Joo; Hill, Stefan; Smith, Dawn; Theobald, Beatrix; Gaugler, Evamaria; Barakat, Abdellatif; Mayer-Laigle, Claire (Frontiers in Chemistry, 2019)
Additive manufacturing or 3D printing has the potential to displace some of the current manufacturing techniques and is particularly attractive if local renewable waste resources can be used. In this study, rice husk and wood powders were compounded in polylactic acid (PLA) by twin screw extrusion to produce filaments for fused-deposition modelling 3D printing. The biomasses were characterized in terms of physical features (e.g. particle size, density) and chemical compositions (e.g. solid state nuclear magnetic resonance, ash content). The two biomasses were found to have a different impact on the rheological behaviour of the compounds and the extrusion process overall stability. When comparing the complex viscosity of neat PLA to the biomass/PLA compounds, the integration of wood powder increased the complex viscosity of the compound, whereas the integration of rice husk powder decreased it. This significant difference in rheological behaviour was attributed to the higher specific surface area (and chemical reactivity) of the rice husk particles and the presence of silica in rice husks compared to the wood powder. Colour variations were also observed. Despite the biomass filler and rheological behaviour differences, the mechanical properties of the 3D printed samples were similar and predominantly affected by the printing direction.